Parents views on children’s physical vulnerability to Covid-19 pandemic - Sejuti, Sadia Jebin; Banik, Bijoy Krishna (Universitas Airlangga, 2024)
This study focuses on the physical vulnerability of the young children. There was a strict lockdown in Rajshahi City, like in other districts of Bangladesh, during the Covid-19 pandemic. Schools were closed for almost two years to keep children safe. Conscious parents did not allow them to go outside. So, children were deprived of the opportunity to grow up in a free environment. This data was collected by using a mixed method, which was collected after the lockdown restrictions were lifted. Data were collected in this study from 05 April 2022 to 28 September 2022 by visiting urban residents. Mothers thought that children’s use of phones, playing video games, and watching cartoons on TV had increased at home confinement, and later, it became their habit. That hampered their eyesight. Children were more insistent and arrogant if they were not allowed to play video games. They were victims of humiliating punishment by family members. They did not go to sleep at the right time and did not follow the routine of sports, studies, and eating home-cooked food. That is the negative consequences of staying indoors. These findings will help policymakers to formulate effective policies for children in the future subsequent epidemic.